2022
DOI: 10.3390/su14138181
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Stakeholder-Oriented Corporate Governance in Achieving Sustainable Development: Evidence from the SME CSR in the Context of China

Abstract: Corporate governance (CG) has been experiencing a shift from the antecedent shareholder-oriented system toward the recent more popular stakeholder-oriented system. To better serve the aim of sustainable development, more and more companies have initiated stakeholder-oriented practices. Increasing social responsibility behaviours demonstrate the prioritisation of stakeholders’ interests. Nevertheless, most extant research on stakeholder-oriented CG focuses on MNEs and large listed companies. Limited attention h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 128 publications
(161 reference statements)
1
2
0
Order By: Relevance
“…The results are in line with those of the other studies in the same area of interest, which indicate that focusing on the important aspect that is better CSR practices and having more consideration for stakeholders, an increase is witnessed in the overall firm performance [55,56]. On the other hand, these results contradict previous studies that suggested enterprises' stakeholderscentered CSR activities have a negative impact on their short-term operational profitability and growth potential [86,[110][111][112], which is also supported by the stewardship theory of the study.…”
Section: Discussionsupporting
confidence: 83%
“…The results are in line with those of the other studies in the same area of interest, which indicate that focusing on the important aspect that is better CSR practices and having more consideration for stakeholders, an increase is witnessed in the overall firm performance [55,56]. On the other hand, these results contradict previous studies that suggested enterprises' stakeholderscentered CSR activities have a negative impact on their short-term operational profitability and growth potential [86,[110][111][112], which is also supported by the stewardship theory of the study.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, the guidelines for the industrial sector for SMEs include no more than 2,000 employees and an annual turnover of a maximum of RMB 300 million. Their total assets must not exceed 400 million RMB ( Zhang et al, 2022 ).…”
Section: Review Of Literature and Development Of Hypothesesmentioning
confidence: 99%
“…Sustainable development is achieved by performing well in terms of the economic, social, and environmental pillars [42]. As such, all nations are mandated to achieve sustainable development goals to ensure that human needs are balanced with the regeneration rate of the environment [42,43]. It becomes vital to define sustainability to understand sustainable development at the firm level.…”
Section: The Concept Of Sustainable Development and Sustainabilitymentioning
confidence: 99%
“…Firms should not view the sustainability call as a threat to business viability, but rather as a scope within which to unlock new opportunities [31]. In this case, the best environmental sustainability strategy should leverage clear green policies and green practices shared by all organisational members and other stakeholders [33,36,43]. This ensures that everyone understands the strategy, making it easier to implement and achieve the expected results [52].…”
Section: The Concept Of Sustainable Development and Sustainabilitymentioning
confidence: 99%